2019
DOI: 10.1055/a-0746-3520
|View full text |Cite
|
Sign up to set email alerts
|

Quality of endoscopy reporting at index colonoscopy significantly impacts outcome of subsequent EMR in patients with > 20 mm colon polyps

Abstract: Background and study aims Endoscopic mucosal resection (EMR) is safe and cost-effective in management of patients with colon polyps. However, very little is known about the actions of the referring endoscopist following identification of these lesions at index colonoscopy, and the impact of those actions on the outcome of subsequent referral for EMR. The aim of this study was to identify practices at index colonoscopy that lead to failure of subsequent EMR. Patients and methods Two hundred and eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This IPDMA involving 8229 colorectal polyps from 13 studies shows that prophylactic clipping in general did Our findings are in accordance with recent studies on prophylactic clipping that concluded that prophylactic clipping should not be routinely performed after polyp resection in the whole colon, but should be considered for bleeding prevention after large proximal polyp resection. 8,9,12,26,30,31 Based on this, it can well be concluded that in a setting where cost issues do not play an important role, all proximal polyps 20 mm may be routinely clipped. Nonetheless, costs considerations often are an important factor in general care settings.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This IPDMA involving 8229 colorectal polyps from 13 studies shows that prophylactic clipping in general did Our findings are in accordance with recent studies on prophylactic clipping that concluded that prophylactic clipping should not be routinely performed after polyp resection in the whole colon, but should be considered for bleeding prevention after large proximal polyp resection. 8,9,12,26,30,31 Based on this, it can well be concluded that in a setting where cost issues do not play an important role, all proximal polyps 20 mm may be routinely clipped. Nonetheless, costs considerations often are an important factor in general care settings.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of delayed bleeding varies from 0.4% to 12.7% 2,3 and increases with polyp size and type, location in the colon proximal to the splenic flexure, polyp type, antithrombotic, use and in patients on antithrombotics. [3][4][5][6][7][8][9][10] Prophylactic clipping has been suggested to prevent delayed bleeding, but contradicting results have been reported. 2,[9][10][11][12] Clip closure is defined as the placement of 1 or more clips to close the mucosal defect after radical polyp resection.…”
Section: Q7mentioning
confidence: 99%
See 3 more Smart Citations